Respostas
respondido por:
1
a1 = a + 3b
a2 = a + b
r = a2 - a1
r = a + b - (a + 3b)
r = a -a + b - 3b
r = - 2b
an = a1 + (n - 1).r
a4 = a1 + (4 - 1).r
a4 = a1 + 3.r
a4 = a + 3b + 3.(-2b)
a4 = a + 3b - 6b
a4 = a - 3b
R.: a4 = a - 3b
a2 = a + b
r = a2 - a1
r = a + b - (a + 3b)
r = a -a + b - 3b
r = - 2b
an = a1 + (n - 1).r
a4 = a1 + (4 - 1).r
a4 = a1 + 3.r
a4 = a + 3b + 3.(-2b)
a4 = a + 3b - 6b
a4 = a - 3b
R.: a4 = a - 3b
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás